Development of a topical therapeutic strategy using corneal derived mesenchymal stromal cells for the treatment of ocular surface disorders - Beeken, Lydia (2023)
Ocular surface inflammatory disorders can lead to serious complications, including vision loss. Current treatments, including eye drops and steroids, are not always effective and can have negative side effects. Mesenchymal stromal cells (MSCs) have shown potential as a regenerative medicine strategy due to their ability to suppress inflammation and promote wound healing. While bone marrow derived MSCs (BM-MSCs) are considered the "gold standard" for MSC therapies, they have limited availability and require invasive harvesting. Alternatively, MSCs from the corneal limbus (CMSCs) can be obtained from corneal transplant surgery waste tissue or eye banks. However, these cells lack necessary characterisation data for clinical translation. This research aimed to extensively characterise CMSCs and assess methods for topical administration of the cells for ocular surface disorders, through functionalisation of the contact lens material poly(HEMA-co-EGDMA).